A Scoping Review and Proposed Framework for Coping in Youth With a History of Psychological Trauma and Chronic Pain. (3rd December 2021) - Nelson, Sarah; Agoston, Monica; Kovar-Gough, Iris; Cunningham, Natoshia
Abstract: Objective: Psychological trauma (e.g., abuse, neglect) and posttraumatic stress symptoms (PTSS) commonly occur in pediatric pain populations and may be related to various maladaptive coping strategies, which may in turn affect short- and long-term pain-related outcomes in youth. Accordingly, the current scoping review and conceptual framework seeks to identify important gaps in the field's current understanding of how coping impacts outcomes in youth who have experienced trauma/PTSS and pediatric chronic pain and explores avenues for future investigation. Methods: A scoping review of the literature was performed in Medline, Embase, Cochrane Library, PsycInfo, and Sociological Abstracts. Eligibility criteria included pediatric populations experiencing chronic pain, trauma, adverse childhood events, and/or PTSS and associated coping mechanisms. Nine research papers were selected and used to support the conceptual framework. The framework builds upon the work of Compas et al.'s' model of control-based coping (Compas et al., 2006 ; Compas & Harding Thomsen, 1999 ) and outlines the potential effects of trauma and/or PTSS and pain on coping and pain-related outcomes (e.g., pain chronicity, functional outcomes) in pediatric chronic pain populations. Results: A history of chronic pain and psychological trauma and/or PTSS in youth may contribute to increased risk for maladaptive coping and in turn, poorer pain-related and psychosocial outcomes long-term. Conclusions: Findings from the current scoping review and proposed conceptual framework will guide future research and treatment efforts for youths experiencing pain and trauma and/or PTSS and thereby enhance long-term outcomes.